A novel electrocoagulation electrode configuration for the removal of total organic carbon from primary treated municipal wastewater - Alaa H. Hawari (14151681) (2022)
In this paper, the removal of total organic carbon (TOC) from a primary treated municipal wastewater using a new electrode configuration in electrocoagulation was evaluated. The used electrode configuration induces a dielectrophoretic (DEP) force by using an asymmetrical aluminum electrode with an alternating current power supply. The impact of applied current, electrolysis time, and interelectrode distance on the removal efficiency of TOC were evaluated. The experimental results showed that the maximum removal efficiency of TOC was obtained at 30 min electrolysis time, 600 mA applied current, and 0.5 cm interelectrode distance. Under these operating conditions, the TOC removal was 87.7% compared to 80.5% using symmetrical aluminum electrodes with no DEP effect. The energy consumption at the selected operating conditions was 3.92 kWh/m3. The experimental results were comparable with the simulation results done by COMSOL Multiphysics software. Other Information Published in: Environmental Science and Pollution Research License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11356-020-08678-4